Analisis Sejarah Pemikiran Ekonomi Islam Pada Masa Nabi Muhammad SAW Sampai Masa Kontemporer - Estiana, Isni Nuriyah; Fasa, Muhammad Iqbal; Suharto, Prof (At-Tauzi : Jurnal Ekonomi Islam, 2022)
This article aims to explore Islamic economic thought in the era of the Prophet Muhammad until the contemporary era. Islamic economics is an economic system based on Islamic values ​​based on the holy book of the Qur'an and hadith. The purpose of implementing Islamic economics is to create a civil society. Prophet Muhammad as a role model for all mankind in various aspects of life changed the economic system to bring good for all mankind. Before the Islamic era, the Prophet Muhammad served as a leader and messenger of God so that he changed the country's economic and financial system according to the Qur'an and hadith. Moreover, the Prophet Muhammad was the first pioneer to implement an Islamic economic policy. the first three schools of thought emerge, the Iqtishaduna school, the Mainstream School, and the critical alternative school. key word : Islamic Ekonomic, policy, prophet Muhammad, Mazhab Iqtishaduna; Mazhab Mainstream; Mazhab Alternatif-Kritis.